(untitled) (Applied Biological Research, 2023)
Stone crushing process leads to the emission of huge dust which depletes soil quality and adversely affects the plant growth and development. The present study was aimed to assess the impact of stonecrusher dust on nutrient content and biochemical status of leaves of four widely growing tree species viz. Salix alba, Robinia pseudoacacia, Populus deltoides, and Ailanthus excels in districts Srinagar and Budgam of Kashmir. Leaf samples were collected both from the disturbed and undisturbed sites in separate polythene bags and analysed for micro-and macro nutrients, photosynthetic pigments, carotenoid and ascorbic acid contents. The results revealed low nitrogen content (1.90% in S. alba), phosphorus (0.15% in A. excelsa), potassium (0.25% in R. pseudoacacia) and photosynthetic pigments (total chlorophyll 1.26 mg g-1in A. excelsa), and carotenoid (0.06 mg kg-1in A. excelsa) at disturbed sites of Srinagar and Budgam; while higher contents were recorded at respective control sites. The highest content (in mg kg-1) of Fe (61.54, in S. alba), Mn (38.23, in P. deltoides), Cu (27.54 in P. deltoides), Zn (37.16, in P. deltoides) and ascorbic acid (7.93, in S. alba) was recorded in disturbed site. The study revealed that stone crusher dust dversely affects the leaf physiology, and two plant species viz., S. alba and P. deltoids showed some degree of tolerance todust pollution.